Using the U.S. Test of Financial Literacy in Germany—Adaptation and validation. Issue 2 (3rd April 2017) - Förster, Manuel; Happ, Roland; Molerov, Dimitar
ABSTRACT: In this article, the authors present the adaptation and validation processes conducted to render the American Test of Financial Literacy (TFL) suitable for use in Germany (TFL-G). First, they outline the translation procedure followed and the various cultural adjustments made in line with international standards. Next, they present results from the validation of the TFL-G's content and relations between test scores and external variables, including test takers' prior economic education and interest in economic topics. Preliminary analyses of data gathered from expert interviews and cognitive labs, and the results of the first administration to first-year higher education students ( N = 1, 108) indicate that the TFL-G is a valid instrument to assess young adults' understanding of personal finance in Germany. Perspectives for future research are discussed.